Biological Mechanisms Underlying Voice Changes Due to Dehydration. - Verdolini, Katherine; Min, Young; Titze, Ingo R. (Journal of Speech, Language & Hearing Research, 2002)
Four vocally untrained healthy adults, 2 men and 2 women, completed the study. A double-blind placebo-controlled approach was used to administer three treatments to each participant on separate days. Drugs treatments involved a single 60-mg dose of a diuretic, Lasix (LA), on one day, and a single 50-mg dose of an oral antihistamine, diphenhydramine hydrochloride (DH), on another day. A third day involved the administration of a placebo, sugar pills (SP). Critical posttreatment measures were weight (kg), which estimated systemic dehydration, saliva viscosity (centipoise), which estimated secretion dehydration, and phonation threshold pressure (PTP, in cm H2O), at high pitches, which indicated pulmonary drive for phonation. The central experimental question was: Does systemic dehydration, or secretory dehydration, or both, mediate increases in PTP that are known to occur following dehydration treatments? The results showed that LA induced systemic dehydration, as shown by a decrease in total body mass of about 1%. Weight losses were seen during a 1- to 4-hour block following drug administration and persisted for at least 8 hours thereafter. PTPs also increased in that condition, about 23% relative to baseline, but only several hours after whole-body dehydration was initially seen (5-12 hours after drug administration). In contrast, no evidence was seen that DH accomplished either secretory dehydration or PTP shifts. The results indicate that systemic dehydration can mediate PTP increases. The influence of secretory dehydration on PTP is unclear. Reprinted by permission of the publisher.